The validity and reliability of the violence risk scale-youth version in a diverse sample of violent young offenders - Stockdale, Keira C. (Criminal justice and behavior, 2014)
The Violence Risk Scale?Youth Version (VRS-YV; S. Wong, Lewis, Stockdale, however, results varied among ethnic/cultural, gender, and developmental subgroups. The VRS-YV also demonstrated strong convergent validity with two well-established youth forensic assessment tools. Clinical implications of these findings and future research directions are discussed in this article.